Human-AI Teaming: State-of-the-Art and Research Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Although artificial intelligence (AI) has many potential benefits, it has also been shown to suffer from a number of challenges for successful performance in complex real-world environments such as military operations, including brittleness, perceptual limitations, hidden biases, and lack of a model of causation important for understanding and predicting future events. These limitations mean that AI will remain inadequate for operating on its own in many complex and novel situations for the foreseeable future, and that AI will need to be carefully managed by humans to achieve their desired utility. Human-AI Teaming: State-of-the-Art and Research Needs examines the factors that are relevant to the design and implementation of AI systems with respect to human operations. This report provides an overview of the state of research on human-AI teaming to determine gaps and future research priorities and explores critical human-systems integration issues for achieving optimal performance.
Keywords: Behavioral and Social Sciences

The Future of Education Research at IES: Advancing an Equity-Oriented Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2002 Congress passed the Education Sciences Reform Act of 2002 (ESRA), authorizing the creation of the Institute of Education Sciences (IES) as the research, evaluation, statistics, and assessment arm of the Department of Education, and crystallizing the federal government's commitment to providing national leadership in expanding fundamental knowledge and understanding of education from early childhood through postsecondary study. IES shares information on the condition and progress of education in the United States, including early childhood education and special education; educational practices that support learning and improve academic achievement and access to educational opportunities for all students; and the effectiveness of federal and other education programs. In response to a request from the Institute of Education Sciences, this report provides guidance on the future of education research at the National Center for Education Research and the National Center for Special Education Research, two centers directed by IES. This report identifies critical problems and issues, new methods and approaches, and new and different kinds of research training investments.
Keywords: Education